Importance of social and cultural factors for attitudes, disclosure and time off work for depression: findings from a seven country European study on depression in the workplace. - Sara Evans-Lacko (Public Library of Science (PLoS), 2014)
Objectives Depression is experienced by a large proportion of the workforce and associated with high costs to employers and employees. There is little research on how the social costs of depression vary by social and cultural context. This study investigates individual, workplace and societal factors associated with greater perceived discomfort regarding depression in the workplace, greater likelihood of employees taking time off of work as a result of depression and greater likelihood of disclosure of depression to one's employer. Methods Employees and managers (n = 7,065) were recruited from seven European countries to participate in the IDEA survey. Multivariable logistic regression models were used to examine associations between individual characteristics and country contextual characteristics in relation to workplace perceptions, likelihood of taking time off work and disclosing depression to an employer. Results Our findings suggest that structural factors such as benefit systems and flexible working hours are important for understanding workplace perceptions and consequences for employees with depression. However, manager responses that focus on offering help to the employee with depression appear to have stronger associations with positive perceptions in the workplace, and also with openness and disclosure by employees with depression. Conclusion This study highlights the importance of individual, workplace and societal factors that may be associated with how people with depression are perceived and treated in the workplace, and, hence, factors that may be associated with openness and disclosure among employees with depression. Some responses, such as flexible working hours, may be helpful but are not necessarily sufficient, and our findings also emphasise the importance of support and openness of managers in addition to flexible working hours.